2019
DOI: 10.1080/17517575.2019.1670361
|View full text |Cite
|
Sign up to set email alerts
|

Health condition estimation of spacecraft key components using belief rule base

Abstract: This paper proposes a method for estimating the health status of spacecraft key components based on the belief rule base (BRB), a semi-quantitative method which uses both human judgmental information and numerical data. It not only allows experts to establish rules to provide useful conclusions, but also allows historical data to train its parameters to obtain more accurate outputs. To balance the parameter training and experts' knowledge, the Markov Chain Monte Carlo (MCMC) technique instead of traditional op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In addition, in practice, battery systems often experience temperature variations during operation. Understanding how temperature variations, even subtle ones, interact with other factors that affect capacity degradation is critical to practical battery health assessment and predictive maintenance 29 . The battery capacity was chosen as the health indicator.…”
Section: Experimental Researchmentioning
confidence: 99%
“…In addition, in practice, battery systems often experience temperature variations during operation. Understanding how temperature variations, even subtle ones, interact with other factors that affect capacity degradation is critical to practical battery health assessment and predictive maintenance 29 . The battery capacity was chosen as the health indicator.…”
Section: Experimental Researchmentioning
confidence: 99%
“…When an unmanned space system was deployed, it was critical to monitor its health condition dynamically of critical components to ensure safe and normal operations. Tang et al [84] suggested using belief rules to assess health conditions of critical components in spacecraft; Shi et al [85] introduced an integrated approach for fault diagnosis of spacecraft. Song et al [86] discussed the correspondence of acquired data and the health conditions of spacecraft for the recognition of system health status.…”
Section: A Sensing Technologiesmentioning
confidence: 99%
“…We choose the equal discharge voltage difference time interval (TIEDVD), the mean temperature (MT) during the discharge process [33], the mean voltage falloff (MVF) [34] and the discharge dump time (DDT) as characteristic features of the battery health indicator. We choose the battery capacity as the health indicator.…”
Section: ) Battery Dataset From Nasamentioning
confidence: 99%
“…The experiment stops when the battery capacity reaches 80% of the rated capacity. We choose the TIEDVD [33], the DDT and the MVF [34] as characteristic features. The capacity 9 degradation curve of the battery is shown in Fig.…”
Section: ) Battery Dataset From Calcementioning
confidence: 99%